Modification of Coronary-Prone Behaviors in Coronary Patients of Low Socio-Economic Status - Del Pino, Antonio; Gaos, Mª Teresa; Dorta, Ruth; García, Martín (The Spanish Journal of Psychology, 2005)
The purpose of this study is to determine the effectiveness of a group cognitive-behavioral treatment to modify coronary-prone behaviors in patients from a fairly low social and educational level. Participants were 98 male coronary patients randomly allocated to one experimental and two control groups. All groups received standard medical treatment. The experimental group received an additional psychological treatment and one of the two control groups received a health education treatment. Results showed that only the psychological treatment group significantly reduced Pressured Drive and Speed-Impatience after treatment, and at 1- and 2-year follow-ups. Depression was also significantly reduced only in this group at 2-year follow-up. The results are considered a reliable first step in the process of validating this program designed to improve coronary heart disease patients’ quality of life.